Impact of tinnitus on quality of life: a review - Swain, Santosh Kumar (International Journal of Advances in Medicine, 2021)
Tinnitus is a poorly understood disorder in medicine. Tinnitus is an auditory perception of the sound in the ear or head in the absence of the external or internal stimuli. It is a common medical symptom which can be debilitating to all age group although frequently associated with elderly individuals. Tinnitus may be associated with lower health related quality of life (HRQoL). Tinnitus is a disturbing otological symptoms and often associated with hearing loss. The risk factors for tinnitus are hearing loss, ototoxicity, head injury and depression. It poses a challenge to the quality of the life. Tinnitus is a symptom which can be associated with various diseases of the external, middle or inner ear, brain stem and cerebral cortex. Tinnitus is frequently seen clinical finding and its adversity affects the quality of life in relatively small proportions of the individuals. The quality of the life is often affected in terms of psychological or emotional effects, sleep disturbance, auditory and health effects. Tinnitus can be debilitating to the sufferers. The quality of the life is often affected in terms of psychological or emotional effects, sleep disturbance, auditory and health effects. Hearing assessment and evaluation of quality of life should be advocated in routine assessment of the tinnitus patients. The objective of this study was to discuss the impact of tinnitus on quality of life.